Keragaman Genetik Bawang Merah (Allium cepa L.) Berdasarkan Marka Morfologi dan ISSR - Sari, Vebrita; ,, Miftahudin; Sobir, dan (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
Development of new shallot varieties requires genetic variation of the germplasm. However, information on genetic diversity of local shallot in Indonesia is still lacking. This study was aimed to analyze the genetic diversity of shallot based on morphological characters and ISSR markers for management of genetic resource and breeding program in Indonesia. This study was conducted during October 2014 to September 2015. The 34-shallot genotypes were collected from several regions in Indonesia in the form of the bulb. Twenty four morphological markers and 13 ISSR primers were used in this research. The informative characters to analyze genetic diversity of shallot were foliage cracking, bulb number and bulb morphological characters. ISSR markers generated 103 DNA polymorphic band with the total of 89.57% and the informative primers were ISSRred 4, ISSRred 9 and ISSRred 20. Both morphological and ISSR markers showed 27% genetic diversity and grouped all genotypes into two main groups; however the grouping did not relate to the geographic origin. The largest bulb diameter of 7.54 cm was obtained from Bangkok variety and the highest number of bulb per clump of 27 bulb/clump was produced by the genotype from Pekanbaru. These genotypes can be used as potential parents for shallot breeding program in Indonesia. Keywords: genetic diversity, ISSR markers, morphological characters, shallot